2016
DOI: 10.2340/00015555-2298
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital Human Papillomavirus Prevalence is Unaffected by Therapeutic Tumour Necrosis Factor-alpha Inhibition

Abstract: Patients receiving tumour necrosis factor alpha (TNF-α) inhibitors are at increased risk of exacerbation of (myco-)bacterial and some viral infections. However, information on anogenital human papillomavirus (HPV) infection in these patients is sparse or conflicting. In this study 222 patients with psoriasis or inflammatory bowel disease (IBD), who received either anti-TNF-α inhibitors or alternatives (purine-, folic acid analogues, phototherapy, fumaric ester, mesalazine) continuously for at least 6 months, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
16
1
2
Order By: Relevance
“…Compared with patients not receiving immunosuppressive treatment, patients with IBD receiving azathioprine show a higher incidence of cutaneous warts and skin and genital herpes flares [59]. Although some studies have reported the development or worsening of genital condyloma in patients with IBD treated with anti-tumour necrosis factor (TNF) antibodies such as infliximab and etanercept [60,61], other studies suggest no relationship between the use of TNF antibodies and persistent HPV infection [62].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with patients not receiving immunosuppressive treatment, patients with IBD receiving azathioprine show a higher incidence of cutaneous warts and skin and genital herpes flares [59]. Although some studies have reported the development or worsening of genital condyloma in patients with IBD treated with anti-tumour necrosis factor (TNF) antibodies such as infliximab and etanercept [60,61], other studies suggest no relationship between the use of TNF antibodies and persistent HPV infection [62].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from some rare skin diseases, a high prevalence of HPV infections is also related to the treatment of psoriasis with psoralen-ultraviolet-A but not with tumor necrosis factor alpha inhibitors. 6,7 However, in our case, the patient had not received any of these treatments in the past 3 years before having anogenital warts. Carnero et al 8 reported a case of multiple warts on psoriasis plaques and considered HPV to be involved in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 60%
“…Apart from some rare skin diseases, a high prevalence of HPV infections is also related to the treatment of psoriasis with psoralen‐ultraviolet‐A but not with tumor necrosis factor alpha inhibitors 6,7 . However, in our case, the patient had not received any of these treatments in the past 3 years before having anogenital warts.…”
Section: Discussionmentioning
confidence: 66%